-9z-z=6z-8+6z

Simple and best practice solution for -9z-z=6z-8+6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9z-z=6z-8+6z equation:


Simplifying
-9z + -1z = 6z + -8 + 6z

Combine like terms: -9z + -1z = -10z
-10z = 6z + -8 + 6z

Reorder the terms:
-10z = -8 + 6z + 6z

Combine like terms: 6z + 6z = 12z
-10z = -8 + 12z

Solving
-10z = -8 + 12z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-12z' to each side of the equation.
-10z + -12z = -8 + 12z + -12z

Combine like terms: -10z + -12z = -22z
-22z = -8 + 12z + -12z

Combine like terms: 12z + -12z = 0
-22z = -8 + 0
-22z = -8

Divide each side by '-22'.
z = 0.3636363636

Simplifying
z = 0.3636363636

See similar equations:

| 45=3x-2x-10 | | 8x-5-3x=6x-8 | | 12x-93=5x-9 | | X/4-9=-16 | | Ln(x)+2*x=0 | | 2x+4(x-6)=3(x+2) | | -3(2y+5)+4(3y-6)= | | -8+7+4x=69 | | 7m-25=2n | | 3x^6-24x^3=0 | | 7x-42=2x+38 | | 2z-7z=-z-1-9z | | 4x+9+x=-6 | | 8m-4=8m | | -15x-15=90 | | X-2.16=9.87 | | 12x-12=4+6x | | 3/x=9/25 | | X-9.7=7.8 | | 29,000,000/X=8.57 | | 9z+6z=7z-6+3z | | -3(4t+5)+7(3t-4)= | | -6(3x-4)=120 | | t−8=5(t/3−8 | | 86=x+6x+9 | | 18x+6=2x-9x | | 9x/5-33=3 | | 73=4x+5x+10 | | 6a+18=0 | | x+124=431 | | 0.2(d-2)=0.3d+5-3+0.1d | | 3(x+4)+4(7x-3)= |

Equations solver categories